Alleviation by abscisic acid of Al toxicity in rice bean is not associated with citrate efflux but depends on ABI5‐mediated signal transduction pathways. Issue 2 (18th September 2018) - Fan, Wei; Xu, Jia Meng; Wu, Pei; Yang, Zhi Xin; Lou, He Qiang; Chen, Wei Wei; Jin, Jian Fen; Zheng, Shao Jian; Yang, Jian Li
Abstract: Under conditions of aluminum (Al) toxicity, which severely inhibits root growth in acidic soils, plants rapidly alter their gene expression to optimize physiological fitness for survival. Abscisic acid (ABA) has been suggested as a mediator between Al stress and gene expression, but the underlying mechanisms remain largely unknown. Here, we investigated ABA‐mediated Al‐stress responses, using integrated physiological and molecular biology approaches. We demonstrate that Al stress caused ABA accumulation in the root apex of rice bean ( Vigna umbellata [Thunb.] Ohwi & Ohashi), which positively regulated Al tolerance. However, this was not associated with known Al‐tolerance mechanisms. Transcriptomic analysis revealed that nearly one‐third of the responsive genes were shared between the Al‐stress and ABA treatments. We further identified a transcription factor, ABI5, as being positively involved in Al tolerance. Arabidopsis abi5 mutants displayed increased sensitivity to Al, which was not related to the regulation of AtALMT1 and AtMATE expression. Functional categorization of ABI5‐mediated genes revealed the importance of cell wall modification and osmoregulation in Al tolerance, a finding supported by osmotic stress treatment on Al tolerance. Our results suggest that ABA signal transduction pathways provide an additional layer of regulatory control over Al tolerance in plants. Abstract : ABA is positively involved in the regulation of Al tolerance in rice bean. Here we showed that this regulation depends on ABI5‐mediated cell wall modification and osmo‐regulation rather than known mechanism of organic acids secretion.